Evaluation of risk factors for recurrent primary common bile duct stone in patients with cholecystectomy. (3rd April 2018) - Yoo, Eun Soo; Yoo, Byung Moo; Kim, Jin Hong; Hwang, Jae Chul; Yang, Min Jae; Lee, Kee Myung; Kim, Soon Sun; Noh, Choong Kyun
Abstract: Objectives: Recurrence of primary common bile duct (CBD) stone commonly occurs after complete removal of CBD stones in patients with cholecystectomy. This study aimed to investigate potential risk factors for the recurrence of primary CBD stones after endoscopic treatment. Materials and methods: Between January 2005 and December 2015, the endoscopic retrograde cholangiopancreatography (ERCP) database of our medical center was retrospectively reviewed; information regarding eligible patients who had recurrent CBD stones with a history of previous cholecystectomy was collected. The characteristics of the patients, CBD stone, CBD and ERCP-related factors were analyzed. Results: The recurrence rate of CBD stone was 18.5% (115/622) after endoscopic treatment in patients with cholecystectomy. In univariate analysis, the number of CBD stones (≥2), CBD stone diameter (≥10 mm), stone composition, stone consistency, CBD diameter (≥15 mm), bile duct dilatation pattern, sharp bile duct angulation (<145°), balloon dilatation, large balloon (>12 mm) dilatation, endoscopic mechanical lithotripsy, endoscopic sphincterotomy, and endoscopic papillary balloon dilatation alone method were significant between the non-recurrence and recurrence groups. However, in multivariate analysis (based on the binary logistic regression method), the number of CBD stones (≥2) (adjusted odds ratio [AOR] 3.232; 95% confidence interval [CI] 1.344–7.773; p = .009), cholesterol stone (AOR 2.824; 95% CI 1.175–6.786; p =.02) and sharp bile duct angulation (<145°) (AOR 2.462; 95% CI 1.062–5.711; p = .036) were independent risk factors of CBD stone recurrence after cholecystectomy. Conclusions: CBD stone number (≥2), cholesterol stone and sharp bile duct angulation (<145°) are associated with recurrent common bile duct stones after cholecystectomy.